Perilaku Pencarian Informasi Guru Terhadap Penggunaan Media Pembelajaran Berbasis Digital di SMP Negeri 25 Kota Padang - Dwi Yudita Putri; Rini Asmara (Lembaga Teewan Journal Solutions, 2026)
Digital transformation in Indonesia’s education sector has driven an increase in the use of digital learning media by educators, which has significantly influenced changes in information-seeking patterns to support learning activities. The purpose of this study is to analyze teachers’ information-seeking behavior regarding the use of digital learning media at SMP Negeri 25 in Padang. This study employed a descriptive quantitative method with a sample of 46 participants selected through total sampling. Data collection was conducted through a questionnaire designed based on the Marchionini model, namely understanding, plan and execution, and evaluation and use. Data were analyzed using frequency distributions and mean score calculations with the aid of SPSS. The results indicate that the “understanding” aspect of information seeking was very high, with a mean score of 3.33. The “plan and execution” aspect was in the high category, with a score of 3.11. Meanwhile, the “evaluation and use” aspect regarding information utilization was in the very high category, with a score of 3.29. These results indicate that, in general, teachers’ information-seeking behavior regarding the use of digital-based learning media at SMP Negeri 25 Kota Padang falls into the high category. However, improvements are still needed in the planning and execution aspects of information seeking to make it more effective, particularly in the ability to formulate keywords